2020
DOI: 10.1590/s1678-3921.pab2020.v55.01836
|View full text |Cite
|
Sign up to set email alerts
|

Damage assessment and economic injury level of the two-spotted spider mite Tetranychus urticae in soybean

Abstract: The objective of this work was to quantify the reduction of soybean grain yield caused by Tetranychus urticae damage, and to propose an economic injury level (EIL) for this pest in the crop. The experimental design was set up in randomized complete blocks, with four replicates and a 4x2 factorial arrangement with four levels of mite infestation, with or without mite control. Chlorotic symptoms were evaluated using a damage scale of 1 to 4. Soybean grain yield, number of pods, number of grains, and 1,000-grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The leaf S2. Values are mean ± SD (n = 3) (grey shaded area) area damage and the abundance of two-spotted spider mites were not evaluated in 2017, but Padilha et al (2020) calculated a decrease in soybean yield of one pod plant −1 , 0.7 g TKM, and 0.42 g m −2 by an infestation rate of one spi-der mite leaf area cm −2 . However, the observed grain yield components in the current study showed that soybean had a high potential of adaptation and indicates grain density as a robust parameter over both years.…”
Section: Soybean Yield Components Plant Growth and Weather Conditionsmentioning
confidence: 99%
“…The leaf S2. Values are mean ± SD (n = 3) (grey shaded area) area damage and the abundance of two-spotted spider mites were not evaluated in 2017, but Padilha et al (2020) calculated a decrease in soybean yield of one pod plant −1 , 0.7 g TKM, and 0.42 g m −2 by an infestation rate of one spi-der mite leaf area cm −2 . However, the observed grain yield components in the current study showed that soybean had a high potential of adaptation and indicates grain density as a robust parameter over both years.…”
Section: Soybean Yield Components Plant Growth and Weather Conditionsmentioning
confidence: 99%
“…The population dynamics of T. urticae showed that infestation increased gradually from mid-June day reached its maximum at the end of July, and then decreased gradually at the beginning of Aug., reached its minimum number at the beginning of Sept. before the harvest time. Padilha et al (2020) reported the reduction of soybean grain yield caused by T. urticae damage. The population density of one T. urticae per cm 2 of leaf area caused the following reductions: one pod per plant, two grains per plant, 0.7 g of 1,000-grain weight, and 0.35 g of grain yield per plant or 42 kg ha -1 .…”
Section: Population Fluctuation Of E Scutalis During 2015-2016 Growing Seasonsmentioning
confidence: 99%
“…The two‐spotted spider mite, Tetranychus urticae Koch (Acarina, Tetranychidae), is a highly damaging agricultural pest around the world (Bamel & Gulati, 2021; Padilha et al, 2020; Sun et al, 2012; Tehri, 2014) with remarkable dispersal abilities (Smitley & Kennedy, 1985). It has become a global concern due to its rapid development, high fecundity, ability to feed on over 1100 plant species, and rapid evolution of pesticide resistance (Grbić et al, 2011).…”
Section: Introductionmentioning
confidence: 99%